Culinary Potential in The Colorful Village of Tigarihit in Simalungun District - Zaitun, Zaitun; Dalimunthe, M.Yusuf (Cattleya Darmaya Fortuna, 2024)
This research has three research objectives, namely: (1) Looking at the condition of the facilities and supporting facilities that currently exist in the colorful village tourism of Tigarihit, (2) compiling a detailed inventory of culinary potential which includes: (a) Types of traditional food (b) Traditional food processing methods, (c) Economic aspects and (d) Documentation, (3) Arrange alternative development of culinary potential in the colorful village tourism village. This type of research is survey research with descriptive methods. Based on the survey conducted in Parapat City, a total of 6 types of traditional food were identified. The main ingredients most widely used to make traditional foods are chicken and fish (80%), then other ingredients (20%). Traditional Simalungun food, based on the way it is processed can be categorized into four, namely: (1) steamed, (2) fried, (3) grilled, and (4) boiled. Based on the results of interviews with traditional food sources in Simalungun, some alternative developments that can be done are the Identification and inventory of traditional foods, compiling profiles of traditional foods in the region as information and promotion materials, encouraging the development of traditional food centers with related agencies, the private sector and the community; Providing soft credit for additional capital